Beliefs and practices of Malaysian Indians on the concept of the divine - Hinduja Jayer Raman, R.J. (2014)

(untitled)
A belief system is a subpart of the cultural elements of society. It is divided into a number of types. One type of belief shared universally is the one relating to the concept of the divine. Even though this is a universal belief, its practice differs from one group to another, until it forms a type of identity unique to that community. This phenomenon also occurs among Malaysian Indians, where the belief principles and practices relating to the concept of the divine are unique. This is seen in current study, based on Malaysian Tamil dramas shown on the Astro Vaanavil channel. This study will most likely contribute to existing literature on the belief system of Malaysian Indians relating to the concept of the divine